The genome sequence of the Triangle-marked Roller, Ancylis achatana (Denis & Schiffermüller), 1775 [version 1; peer review: 2 approved, 1 approved with reservations] - Douglas Boyes; Clare Boyes; David C. Lees (Wellcome Open Research)
We present a genome assembly from a male specimen of Ancylis achatana (Triangle-marked Roller; Arthropoda; Insecta; Lepidoptera; Tortricidae). The genome sequence has a total length of 547.27 megabases. Most of the assembly (99.25%) is scaffolded into 28 chromosomal pseudomolecules, including the Z sex chromosome. The mitochondrial genome has also been assembled, with a length of 16.0 kilobases.